2015
DOI: 10.1080/09602011.2015.1105825
|View full text |Cite
|
Sign up to set email alerts
|

A sublexical training study for spelling in a biliterate Greek- and English-speaking child

Abstract: RI is an emergent trilingual boy, literate in Greek and English, with difficulties in reading and spelling in both languages. Assessment with non-literacy tests revealed a deficit in phonological ability and in visual memory for sequentially presented characters. RI took part in a training programme that targeted sublexical spelling processes. Post-intervention assessment revealed improvement in reading and spelling in Greek but not in English. Assessments of lexical and sublexical skills showed improvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 48 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…In addition, we were able to find that raising awareness of spelling patterns and rules and combining this with phonological training can have a substantial positive impact on spelling and reading (Apel & Masterson, 2001;Treiman & Kessler, 2014;Treiman, 2017). Other researchers in the past, have suggested that training in spelling can generalise to reading (Niolaki et al, 2017;Kohnen et al, 2008) and we were also able to confirm that through our intervention. However, it is also interesting to note the Georgiou, Torppa, Landerl, Desrochers, Manolitsis, de Jong, and Parrila (2020) in a cross-linguistic longitudinal study exploring the bidirectional links between spelling and reading performance in Grade 1 and 2 children did not find a predicted link from spelling to reading, whereas the opposite was observed in our study.…”
Section: Interventionsupporting
confidence: 74%
See 4 more Smart Citations
“…In addition, we were able to find that raising awareness of spelling patterns and rules and combining this with phonological training can have a substantial positive impact on spelling and reading (Apel & Masterson, 2001;Treiman & Kessler, 2014;Treiman, 2017). Other researchers in the past, have suggested that training in spelling can generalise to reading (Niolaki et al, 2017;Kohnen et al, 2008) and we were also able to confirm that through our intervention. However, it is also interesting to note the Georgiou, Torppa, Landerl, Desrochers, Manolitsis, de Jong, and Parrila (2020) in a cross-linguistic longitudinal study exploring the bidirectional links between spelling and reading performance in Grade 1 and 2 children did not find a predicted link from spelling to reading, whereas the opposite was observed in our study.…”
Section: Interventionsupporting
confidence: 74%
“…Georgiou et al utilised younger typically performing children, thus, for children who have already developed good reading and spelling skills, this direction from spelling to reading might not be on a par to the significance of the direction for children who struggle with reading and spelling, like AM. Children with dyslexia will use any support given to strengthen the links between phonology and orthography and vice versa and especially when this is coupled with explicit teaching or morphological rules and orthographic patterns (see for similar results Conrad 2008;Niolaki et al, 2017;Kohnen et al, 2008).…”
Section: Interventionmentioning
confidence: 92%
See 3 more Smart Citations